Analisis Dampak Kebijakan Impor Gula: Studi Kasus Implementasi dan Konsekuensi Jangka Panjang - Janeska Widia (Konsensus : Jurnal Ilmu Pertahanan, Hukum dan Ilmu Komunikasi, 2025)
This research examines the impact of Indonesia's sugar import policy during the period 2020–2024 through the case study of Thomas Trikasih Lembong. Employing a qualitative methodology with an instrumental case study approach, the study seeks to capture the complexities of strategic commodity trade policies in Indonesia. The analysis reveals that the issuance of sugar import permits to PT Andalas Putra was conducted in violation of existing legal frameworks, particularly Presidential Regulation No. 48/2013, resulting in state financial losses estimated at Rp 400 billion. These irregularities highlight not only weak adherence to regulatory standards but also minimal coordination among relevant government agencies, reflecting the broader challenge of weak good governance implementation. The distributional consequences of this policy were also significant. While downstream industries benefited from increased sugar availability and lower input costs, domestic sugarcane farmers and the national sugar industry suffered substantial losses. The oversupply condition triggered by import policy mismanagement led to a decline in local sugar prices, producing welfare transfers that disproportionately disadvantaged rural farming communities. These findings underscore the structural vulnerability of agricultural stakeholders when state institutions fail to balance industrial and farming interests in policy formulation. Furthermore, the imposition of a 4.5-year prison sentence on the policymaker involved has sparked discourse on the criminalization of public policy, raising debates over the line between policy failure and corruption in governance. In light of these findings, the study provides several recommendations. These include strengthening inter-agency coordination mechanisms, developing early warning systems to monitor commodity market dynamics, reforming the regulatory framework governing import permits, and designing adaptive policy instruments capable of mitigating welfare risks while optimizing strategic commodity management. Overall, this study contributes to the discourse on governance, accountability, and policy reform in Indonesia’s strategic trade sector, particularly in relation to sugar as a vital commodity.